Characterization of IDC FEF fingers for pH sensor - Rahmat, Muhammad Haniff (2011)
This paper presents a study of making a pH sensor by using planar fringing field effect. This FEF sensor study is carried out by using Inter Digital Capacitor (IDC) technique on Printed Circuit Board (PCB). The main objective is to investigate the effectiveness of using IDC in order to reduce the cost of making pH sensor. This study focused on the effect of using different number of width between finger, length of finger, medium, and effect of ground. This paper also presents simulation and experimental data to characterize the sensor. In addition, the effect of series the IDC also been studied experimentally. The results show that the trend pattern of both simulation and experiment are similar and for the series IDC, the capacitance is decreasing as the number of series IDC increased.